A study on the factor market distortion and the carbon emission scale effect of two-way FDI. Issue 2 (3rd April 2019) - Gong, Mengqi; Liu, Haiyun; Atif, Rao Muhammad; Jiang, Xu
ABSTRACT: Based on the data of 30 Chinese provinces for the period from 2004 to 2015, this paper expounds the carbon emissions effect of two-way foreign direct investment (FDI) from the perspective of scale effect and factor market distortions. This study uses Kaya identity to decompose carbon emission and construct simultaneous equations model to empirically examine the factor market distortion and the carbon emission scale effect of two-way FDI. The results show that the inward foreign direct investment (IFDI) increase regional carbon emission through scale effect and also exacerbates factor market distortion in China, whereas the outward FDI trends reduce carbon emission and reduces factor market distortions in China. The study also shows that human capital, research and development (R&D), trade openness, and capital accumulation are important determinants of two-way FDI. Therefore, the study proposes that IFDI policies should focus on acquiring green technologies. In addition, the domestic enterprises should be encouraged to participate in global business.